Suitability of structure from motion for rock‐slope assessment. (17th May 2018) - O'Banion, Matt S.; Olsen, Michael J.; Rault, Claire; Wartman, Joseph; Cunningham, Keith
Abstract: This study examines three sites in Alaska with unstable rock slopes that were surveyed using both terrestrial laser scanning (TLS) and structure‐from‐motion (SfM) techniques. The datasets were acquired simultaneously and linked to a rigorous survey control network. An accuracy evaluation of the SfM‐derived surface models was performed using the TLS data and numerous reflectorless total station observations collected across the rock slopes. A quality evaluation was conducted to examine differences in point density, model completeness and distributions of morphological properties between the SfM and TLS datasets. The results indicate that SfM is a viable option for unstable rock‐slope assessment when a sufficient number of images with adequate overlap are acquired and the reconstruction is tied to a survey control network. The best results, in terms of accuracy and completeness, were achieved when combining both unmanned aerial vehicle (UAV) and terrestrial imagery for the SfM reconstruction. However, issues such as over‐smoothing and geometric inconsistencies bring into question the suitability of SfM for the detection of small changes over time.